Penegakan Hukum Tindak Pidana Perundungan Atau Bullying Yang Dilakukan Oleh Anak Di Polres Singkawang - Hendradi, Hiznu Octo; Fajrin, M; Hazilina, Hazilina (Res Judicata, 2024)
Abstract Several cases of bullying have recently gone viral after being recorded on camera and spreading in the community. These cases involve children bullying each other, this phenomenon is also influenced by increased social media exposure. Underage perpetrators often face significant social stigmatization, including exclusion from society, verbal abuse, and serious psychological impacts. Therefore, it is important to consider the necessary protections for children who are victims. This study aims to find out how law enforcement against victims of criminal acts of bullying committed by children in the Singkawang City Police and to find out what are the supporting and inhibiting factors in the criminal law enforcement process against the crime of bullying. This research uses an empirical legal research method with a qualitative approach. Data was collected through in-depth interviews with relevant sources and studies of related legal products. The results of the study show that the form of law enforcement against victims of bullying crimes committed by children at the Singkawang City Police is diversion with restorative justice, which is resolving cases in a peaceful and familial way through deliberation. If the victim still takes steps that this case must be processed legally, then the Singkawang Police will conduct an investigation and investigation into the report received. Supporting and inhibiting factors in the criminal law enforcement process against criminal acts of bullying or bullying committed at the Singkawang Police Station are internal and external factors. Internal factors that affect are the availability of personnel both in terms of quantity and quality as well as the availability of facilities and infrastructure. Meanwhile, external factors that affect are regulations or legal provisions and the community in responding to bullying acts. Keywords: Bullying, Law Enforcement, Bullying.